Polish Dialectal Phrasematics – the State of Research (for the Five-year Period 2015–2020), Methods and Perspectives - Rak, Maciej (Vilnius University Open Series, 2021)
The article has three goals. The first is to present the history of research on Polish dialectal phrasematics. In particular, attention was paid to the last five years, i.e. the period 2015–2020. The works in question were ordered according to the dialectological key, taking into account the following dialects: Greater Polish, Masovian, Silesian, Lesser Polish, and the North and South-Eastern dialects. The second goal is to indicate the methodologies that have so far been used to describe dialectal phrasematics. Initially, component analysis was used, which was part of the structuralist research trend, later (more or less from the late 1980s) the ethnolinguistic approach, especially the description of the linguistic picture of the world, began to dominate. The third goal of the article is to provide perspectives. The author once again (as he did it in his earlier works) postulates the preparation of a dictionary of Polish dialectal phrasematics.
Keywords: Polish dialects; dialectal phrasematics; methodologies of phrasematics research